Management of Fournier’s gangrene with skin grafting by bagging technique of testes: case report - AlShehri, Yasir Ali; AlBurshaid, Hiba; AlBassam, Layan; AlMutairi, Khalid (GMS Interdisciplinary Plastic and Reconstructive Surgery DGPW, 2019)
Aim: To share our experience with the management of Fournier gangrene (FG) using the bagging technique of the testes, and to highlight the importance of implementing a multidisciplinary approach in managing FG. Case presentation: A 58-year-old male with type 2 diabetes mellitus (DM) was brought to the emergency department (ED) with necrotizing fasciitis involving the genitalia; he was managed in the ED with Intrave (IV) fluid resuscitation and IV antibiotics. The surgical team was consulted and multiple debridement procedures were done. Healthy granulation tissue was formed within one month of the serial debridement. A split-thickness skin graft using bagging technique of the testes and vacuum-assisted closure (VAC) were applied. The patient was reassessed one year following presentation, and a result with a near normal appearance was achieved with complete preservation of functional outcome.Conclusion: FG is a type of necrotizing fasciitis that could be managed either conservatively with IV antibiotics and/or hyperbaric oxygen, or surgically by debridement and applying VAC.In our case, the testes were debrided and bagging technique of the testes was used. It’s believed that with this technique, the overall cosmetic and functional results are superior.